Delegitimasi Simbol Musik Dalam Upacara Adat Batak Toba - Monang Asi Sianturi (Jurnal Euangelion, 2022)
Abstract: The main concept in the ceremony of the Toba Batak community is a discussion of the awareness that the concept of traditional music is an unchanging variable. This study focuses on the analysis of: 1). The change in the name of the gondang sabangun ensemble is a cultural hybridity that creates a new social space. 2). The atmosphere of the social dynamics of the human mind changes in musical variants according to the changing times. Gondang Sabangun has undergone a change in form, character and appearance that has been adapted to the modern band combo, without changing the cultural structure of the traditional Toba Batak music. Identification of the origin of the song has been a source of inspiration for synthetic changes when compared to changes in popular music used. The view of deconstruction allows new assumptions to be changed by musicians and audiences alike. This study places the cultural identity of Toba Batak music with the ambivalence of changing aesthetic meanings and musical instruments. Awareness between two different views of the present and the past, modern and traditional, external and internal, Western and Batak, gave rise to arguments about the liminal space by placing the concept of Gondang Kombo in the New Social Space. Keywords: traditional ceremony, change, gondang kombo, deconstruction, delegitimation     Abstrak: Konsep utama dalam upacara masyarakat Batak Toba adalah diskusi tentang kesadaran bahwa konsep musik tradisional sebagai variabel yang tidak berubah. Penelitian ini berfokus pada analisis: 1). Perubahan nama ensambel gondang sabangun merupakan hibriditas budaya yang menciptakan ruang sosial baru. 2). Suasana dinamika sosial pikiran manusia berubah dalam varian-varian musik sesuai dengan perubahan zaman. Gondang Sabangunan telah mengalami perubahan bentuk, sifat dan tampilan yang telah disesuaikan dengan kombo band grup musik modern, tanpa mengubah struktur budaya musik tradisional Batak Toba. Identifikasi asal-usul lagu telah menjadi sumber inspirasi perubahan sintetik jika dibandingkan dengan perubahan musik populer yang digunakan. Pandangan dekonstruksi memungkinkan asumsi baru diubah oleh musisi dan penonton. Kajian ini menempatkan identitas budaya musik Batak Toba dengan ambivalensi perubahan makna estetis dan alat musik. Kesadaran antara dua pandangan berbeda masa kini dan masa lalu, modern dan tradisional, eksternal dan internal, Barat dan Batak, memunculkan argumentasi tentang ruang liminal dengan menempatkan kehadiran Gondang Kombo dalam sebuah ruang sosial baru. Kata Kunci: upacara adat, gondang sabangunan, gondang kombo, dekonstruksi, delegitimasi